Proportional resonant current controller strategy in inverter application - Salimin, S.; Noor, A.F.M.; Jumaat, S. A. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper presents the method of proportional resonant current controller strategy in inverter system application. In this study, the mathematical modelling of the controller is shown in detail. This is important for the modelling in Matlab Simulink. Nowadays, the decrement of power quality is easily found in this inverter system where inverter extensively used as interface circuits. To solve this problem, proportional resonant current controller is the solution. At resonant frequency, this controller has infinite gain which ensures a zero steady-state error in a stationary frame. This will result in minimized load current distortion as well as the harmonic contents. At the end, simulation result shows when using PR current controller, the unwanted harmonics injection are much reduced.